Macroeconomic factors of economic growth in the European Union in 2000-2016: A multidimensional analysis - Batóg, Jacek; Batóg, Barbara (Makroekonomiczne czynniki wzrostu gospodarczego w Unii Europejskiej w latach 2000-2016: analiza wielowymiarowa, 2019)
The creation of an effective growth policy requires the identification of its key determinants. The study used one of the methods of multidimensional analysis – discriminant analysis. It is widely used on a microeconomic scale, especially in the area of forecasting bankruptcy of enterprises, but in the area of economic growth, it has not been used in practice so far. In addition to the main objective of identifying the most important economic growth factors of the European Union countries in 2000- 2016, the impact of the crisis and accession to the EU was examined. The statistical data sources were the databases of Eurostat and the Conference Board (Total Economy Database). The results obtained allowed us to conclude that the rate of Gross Domestic Product growth in the EU countries was determined by consumption, investment, export and labour productivity, and in periods of economic slowdown also public debt. The enlargement of the EU resulted in an increase in the importance of export
Econometrics = Ekonometria, 2019, Vol. 23, No. 3, s. 1-14
Keywords: economic growth; discriminant analysis; European Union; economic crisis; wzrost gospodarczy; analiza dyskryminacyjna; Unia Europejska; kryzys gospodarczy